Anomeric Spironucleosides of β-d-Glucopyranosyl Uracil as Potential Inhibitors of Glycogen Phosphorylase - Aggeliki Stathi; Mamais, Michael; Chrysina, Evangelia D.; Gimisis, Thanasis (Molecules, 2019)
In the case of type 2 diabetes, inhibitors of glycogen phosphorylase (GP) may prevent unwanted glycogenolysis under high glucose conditions and thus aim at the reduction of excessive glucose production by the liver. Anomeric spironucleosides, such as hydantocidin, present a rich synthetic chemistry and important biological function (e.g., inhibition of GP). For this study, the Suárez radical methodology was successfully applied to synthesize the first example of a 1,6-dioxa-4-azaspiro[4.5]decane system, not previously constructed via a radical pathway, starting from 6-hydroxymethyl-β-d-glucopyranosyluracil. It was shown that, in the rigid pyranosyl conformation, the required [1,5]-radical translocation was a minor process. The stereochemistry of the spirocycles obtained was unequivocally determined based on the chemical shifts of key sugar protons in the 1H-NMR spectra. The two spirocycles were found to be modest inhibitors of RMGPb.